Childhood Cryptosporidiosis: A Case Report - P. Agnamey; D. Djeddi; A. Diallo; A. Vanrenterghem; N. Brahimi; C. da Costa; A. Totet (Journal of Parasitology Research)
Cryptosporidium has emerged as an important cause of diarrheal illness worldwide, especially amongst young children and patients with infectious or iatrogenic immune deficiencies. The authors describe a case of mild cryptosporidiosis in a well-nourished, immunocompetent, one-year-old child. Rapid clinical and parasitological improvement was observed after a 3-day course of nitazoxanide.